Design of CNC engraving machine production process for acrylic material with working dimensions of 240x400 mm - Bukhari, Bukhari; Teuku Zia Zuliansyah; Edi Saputra (Journal of Mechafa Engineering and Fabrication, 2024)
The design of the CNC engraving machine production process for acrylic material is carried out to meet market demand for products that require special molds or shapes on acrylic materials. This CNC engraving machine has an orientation on materials made from acrylic media and a knife blade for engraving and a drill bit for cutting acrylic. And has dimensions of 51 x 50 cm and has an engraving area of 420 x 400 cm. The equipment used to make CNC machine components consists of a hand drill, cutting grinder, clamping pliers, L-key set, caliper, ruler and meter. The assembly of the CNC Engraving machine used in this study is the Non-Permanent Assembly. The results of the production of mechanical components produced using the machining process have been obtained, consisting of: the lower frame of the machine, the x-axis pole, the work table, the x-axis, the z-axis. The design form that has been made, then the mechanical components that have been produced will be assembled with finished components that are available on the market. The results of the CNC engraving acrylic machine production process take up to 49.2 minutes. The working area of the machine is the length of the x-axis working area = 400 mm, the length of the y-axis working area = 500 mm, the length of the z-axis working area = 120 mm